Remote and Hybrid Working in the Accounting Profession: A Preliminary Systematic Literature Review - Amelia Rizky Alamanda (International Journal of Social Science, 2026)
Remote and hybrid working have become increasingly relevant to the accounting profession, yet evidence on their implications remains fragmented across professional contexts and outcomes. This study systematically reviews the emerging literature to examine the implications of remote and hybrid working for accounting professionals and practice. Following PRISMA 2020, relevant journal articles published between 2022 and 2026 were identified through Scopus and subjected to eligibility assessment and qualitative synthesis. The evidence shows that remote working involves both benefits and challenges across individual, relational and professional, and work and audit dimensions. Flexibility, autonomy, and improved work–life balance coexist with reduced social interaction, challenges in professional development and communication, and concerns regarding audit execution and quality. Differences in these outcomes are associated with organizational support, work policies, socialization practices, and technological competency, suggesting that the implications of remote working depend partly on the conditions under which it is implemented. Current evidence remains concentrated in auditing and public accounting and is strongly influenced by pandemic-related working conditions. Further research across accounting roles and established post-pandemic hybrid settings is therefore needed to understand when and under what conditions different working arrangements are effective.